Reimagining Eco Theological Pedagogy: Comparative Analysis of Faith Based Environmental Education Strategies Across Pluralistic School Contexts - Qinta Berliana Valfini; Samsul Ariyadi; Amara Rizki Fadillah (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
Environmental education plays a crucial role in modern curricula, emphasizing sustainability and ecological responsibility to address global challenges. This study compares faith-based and secular environmental education strategies, focusing on how theological reflection and ecological consciousness are integrated into teaching frameworks. Faith-based schools, particularly those rooted in Christianity and Islam, incorporate ecological ethics within religious teachings, framing environmental stewardship as a moral and spiritual duty. In contrast, secular models prioritize scientific literacy and environmental problem-solving. The study reveals that faith-based models promote both scientific understanding and moral engagement with environmental issues through religious values like Imago Dei (in Christian schools) and khalifah (in Islamic schools). These values instill a sense of moral accountability, motivating students to act sustainably. The research also highlights how curriculum design, teacher involvement, and experiential learning contribute to the effectiveness of both models in fostering ecological responsibility. By comparing these approaches, the study proposes an integrative eco-theological pedagogical framework that combines the strengths of both methods to promote long-term commitment to sustainability. The findings have implications for educational policy, curriculum development, and teacher training, especially in pluralistic school settings where diverse perspectives must be considered. Integrating ecological ethics into education can cultivate a generation committed to sustainability and ethical responsibility.